1990s in the history of closed administrative and territorial entities in the nuclear industry through the prism of trauma studies: problem statement - Alfiya Gumarovna Konstantinova (Вестник Майкопского государственного технологического университета, 2023)
The article considers the category of trauma as a specific object of interdisciplinary research, and identifies the signs of historical trauma. Historical trauma is understood as the preserved memory of generations about social upheavals and events that disrupted the usual course of life and transformed the system of basic values. The scientific objectives of the research involved analysis of the events that took place on the territory of the closed administrative and territorial formations of the nuclear industry in the 1990s and can be characterized as a historical trauma. The breakdown of the usual way of life in the determined, artificially created environment of closed cities which was more painful than in a significant part of open cities became the consequence of the all-Russian transient transformational dynamics. The characteristics of the period on the part of the population of atomic cities were often accompanied by themes of physical and domestic survival and social tension. The events that have taken the meanings of trauma place can be described as representing historical significance and having in the collective consciousness. On this basis, the author has concluded that the study of the post-Soviet history of closed administrative-territorial formations of the nuclear industry through the prism of trauma research opens up new perspectives in understanding their development.